Mobile health, physical activity, and obesity: Subanalysis of a randomized controlled trial. Issue 38 (September 2018) - Lee, Chang Hee; Cheung, Booyoon; Yi, Ga-Hye; Oh, Bumjo; Oh, Yun Hwan
Abstract: Background: Recent studies on physical activity were analyzed by randomizing participants into either the intervention or control group. It is necessary to classify each intervention and control groups according to physical activity using the International Physical Activity Questionnaire (IPAQ). Methods: This was a pilot project for SmartCare Services. The intervention group received obesity management services using a smartphone for 24 weeks, while the control group did not receive the interventions. Six anthropometric indices were analyzed: weight, body mass index (BMI), waist circumference, body fat, systolic blood pressure (SBP), and diastolic blood pressure (DBP). Five laboratory tests, including fasting blood sugar (FBS), glycosylated hemoglobin (HbA1c), high-density lipoprotein cholesterol (HDL-C), total cholesterol (TC), and triglycerides (TGs), were also assessed. The final 324 participants were categorized using the IPAQ questionnaire, and anthropometric indices and laboratory tests were analyzed for within-group and between-group changes from baseline to final visit. Results: Statistically significant decreases in the intervention group compared with the control group were observed in terms of insufficient activity (IA) (−1.6 ± 3.03 vs −0.1 ± 1.94 kg) and moderate activity (MA) (−2.5 ± 3.81 vs −0.3 ± 2.24 kg) for weight, IA (−0.7 ± 1.14 vs −0.2 ± 0.93 kg/m 2 ) and MA (−0.9 ± 1.30 vs −0.2 ± 0.86 kg/m 2 ) for BMI, and health-enhancing physical activity (HEPA) (−1.6 ± 3.69% vs −0.1 ± 3.15%) for body fat. For HbA1c, HEPA in the intervention group showed significant decreases (−0.2 ± 0.67 vs 0.0 ± 0.34 mg/dL) compared with the control group. Conclusion: Anthropometric indices and laboratory test results were improved in the smartphone-based intervention group. Especially, improvement of metabolic components in the group with more active physical activity was remarkable.